Tracking Global Social Protection Responses to Price Shocks : Version 1 - Gentilini, Ugo; Almenfi, Mohamed; Iyengar, Hrishikesh TMM; Okamura, Yuko; Urteaga, Emilio Raul; Valleriani, Giorgia; Muhindo, Jimmy Vulembera; Aziz, Sheraz (World Bank, Washington, DC, 2022)
This note provides an update of social protection responses to the food, fuel, fertilizer, and other price shocks sparked or accelerated by the Ukraine war. The vast majority of measures were introduced in early 2022 (February-April), although some specific interventions to mitigate prices were included in late 2021. This initiative complements other two ongoing thematic trackers of country-level action on how social protection is being leveraged in crisis situations – one on Covid-19 responses (16 versions) and another one focused on displacement as a result of the Ukraine war (3 versions). Data is preliminary and meant to elicit comments, additions, integration, and revisions to be incorporated in next living paper versions. Specifically, the note tracks four broad measures, namely social assistance, social insurance, labor markets, and subsidies. The latter includes five subcategories, i.e., fuel, food, fertilizers and agriculture inputs, and fees subsidies. Data and analysis are preliminary, and more information on specific measures will be provided as data becomes available.